President and the legislative process: the use of the veto right in Lithuania - Laimonas Talat-Kelpša (Politologija)
After the Soviet collapse, Lithuania introduced a constitutional model the political scientists usually name as 'semi-presidential regime.' Three principal features characterize semi-presidential government: (1) president-nominated prime minister, (2) presidential power to dissolve parliament, and (3) cabinet reliance on parliamentary support. Beyond doubt, there are other important qualities, such as considerable de jure and de facto presidential powers. Yet the current experience of semi-presidential regimes demonstrates the imbalance that arises (develops) between the de jure and de facto presidential authorities, and one has to acknowledge that as a matter of fact these powers almost never go in accord.